2017
DOI: 10.4049/jimmunol.1600275
|View full text |Cite
|
Sign up to set email alerts
|

PGI2 Controls Pulmonary NK Cells That Prevent Airway Sensitization to House Dust Mite Allergen

Abstract: In allergic asthma, inhalation of airborne allergens such as house dust mite (HDM) effectively activates both innate and adaptive immunity in the lung mucosa. To determine the role of the eicosanoid PGI2 and its receptor IP during allergic airway sensitization, HDM responses in mice lacking a functional IP receptor (IP−/−) were compared to wild type (WT) mice. Surprisingly, IP−/− mice had increased numbers of pulmonary CD3−NK1.1+Ly49b+ NK cells producing IFN-γ that was inversely associated with the number of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 73 publications
(77 reference statements)
4
33
1
Order By: Relevance
“…In a mouse model of Alternaria alternata‐driven severe asthma, PGI2‐receptor deficiency augmented whereas administration of PGI2 analog suppressed IL‐5 and IL‐13 production by lung ILC2s, airway eosinophilia and mucus production score in the airways . The findings of this study, however, were conflicted by a more recent study in which they showed that in the absence of PGI2‐receptor, IFN‐γ producing pulmonary NK cells were expanded, house dust mite‐induced airway eosinophilia and airway mucus production were reduced . It remains to be addressed whether the seeming discrepancy between the two studies are caused by the type of allergen and allergen exposure protocol.…”
Section: Regulation Of Ilc2scontrasting
confidence: 74%
See 1 more Smart Citation
“…In a mouse model of Alternaria alternata‐driven severe asthma, PGI2‐receptor deficiency augmented whereas administration of PGI2 analog suppressed IL‐5 and IL‐13 production by lung ILC2s, airway eosinophilia and mucus production score in the airways . The findings of this study, however, were conflicted by a more recent study in which they showed that in the absence of PGI2‐receptor, IFN‐γ producing pulmonary NK cells were expanded, house dust mite‐induced airway eosinophilia and airway mucus production were reduced . It remains to be addressed whether the seeming discrepancy between the two studies are caused by the type of allergen and allergen exposure protocol.…”
Section: Regulation Of Ilc2scontrasting
confidence: 74%
“…69 The findings of this study, however, were conflicted by a more recent study in which they showed that in the absence of PGI2-receptor, IFNγ producing pulmonary NK cells were expanded, house dust mite-induced airway eosinophilia and airway mucus production were reduced. 70 It remains to be addressed whether the seeming discrepancy between the two studies are caused by the type of allergen and allergen exposure protocol.…”
Section: Regulation Of Ilc2s By Cytokinesmentioning
confidence: 99%
“…However, another study provided different observation that IP‐deficient mice exhibit increased numbers of IFN‐γ − producing NK cells. Considering that IFN‐γ is a negative regulator for ILC2s, NK cell depletion results in a rise in the number of ILC2s in IP‐deficient mice . Thus, PGI2 might directly suppress ILC2s, but also indirectly regulate ILC2s via NK cells.…”
Section: Lipid Mediators (Ltc4 Ltd4 Lte4 Ltb4 Lxa4 Pgd2 Pge2 Amentioning
confidence: 99%
“…Cardinal features of HDM-induced allergic asthma are not influenced by NKp46 + cell absence during the sensitization or challenge phase only In NKp46-DTA mice, ablation of NKp46 + NK cells occurs early during their maturation in the bone marrow (Narni-Mancinelli et al, 2011), raising the possibility of functional replacement of NK cells by other immune cell types during immune development. Moreover, previous studies have suggested that NK cells can fulfill opposing roles during asthma, depending on the models used (Korsgren et al, 1999;Ple et al, 2010;Ghadially et al, 2013;Farhadi et al, 2014;Ferrini et al, 2016;Simons et al, 2017;Wan Jiacheng Bi et al, 2017). We therefore considered the possibility that NK cells might have contrasting roles in the sensitization and challenge phase of the HDM-induced asthma model, which might be obscured in animals constitutively lacking NK cells.…”
Section: Absence Of Nkp46 + Cells Does Not Affect Allergic Asthma Indmentioning
confidence: 99%
“…These studies showed that NK cells were crucial and non-redundant for asthma development induced by ovalbumin (OVA)/alum (Korsgren et al, 1999;Ple et al, 2010;Ghadially et al, 2013) or chronic HDM exposure (Farhadi et al, 2014). In contrast, increased pulmonary NK cell numbers were recently correlated with reduced HDM-mediated airway inflammation in mice (Ferrini et al, 2016;Simons et al, 2017). Moreover, antibody-mediated NK cell depletion was shown to increase eosinophilia and goblet cell hyperplasia in early papain-or bleomycin-induced lung inflammation (Wan Jiacheng Bi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%